The Meaning of the Word Makan in the Banjarese Language as a Treasure of Language Culture - Yayuk, Rissari; Suryatin, Eka; Jamzaroh, Siti (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2023)
The diversity of meanings of a word indicates the treasure of people's knowledge system in the language. This research is to reveal the meaning of one of the words in question, namely, makan, in the Banjar language. The research problem is the meaning of the makan word as a language and cultural treasure in the Banjar people. The study objective is to describe the form of the word makan as a language and cultural wealth in the Banjar people. This research applies qualitative descriptive research methods with observation, note-taking, and documentation techniques. Data collection techniques are uninvolved conversation observation techniques and interviews. The research steps are observation, data collection, sorting, presentation, analysis, and conclusion. The theory related to this research is a semantic, pragmatic, anthropolinguistic approach. The data source is the speech of the Banjar people, who use the word makan. Data collection was in Banjar and Hulu Sungai Selatan Regencies. The collection of data was from June 2021—April 2022. Triangulation of data applies several sources and theories. The data analysis uses miles and Huberman models. The study results show 11 forms of the meaning of eating, swallowing, requiring, utilizing, functioning, damaging, eroding, hurting feelings, spending time, being deceived, and many experiences. The 11 meanings consist of denotations and connotations. The connotation consists of the synecdoche totum pro parte, metaphor, and personification. In conclusion, the results will provide the referral educational material on scientifically documented regional language cultures amid the influence of national and international language dominance.